Prognostic impact of geriatric nutritional risk index on patients with urological cancers: A meta-analysis - Wu, Quan; Ye, Fagen (Frontiers in Oncology, 2023)
Background: Despite previous research examining the predictive value of the geriatric nutritional risk index (GNRI) in individuals with urological cancers (UCs), results have been conflicting. This study aimed to comprehensively explore the potential link between GNRI and the prognosis of UCs using a meta-analysis. Methods: The Cochrane Library, PubMed, Embase, and Web of Science databases were systematically and exhaustively searched. We estimated the prognostic importance of the GNRI in patients with UCs by calculating the pooled hazard ratios (HRs) and 95% confidence intervals (CIs) on survival outcomes. Publication bias was identified using Egger’s test and Begg’s funnel plot. Results: Eight trials with 6,792 patients were included in our meta-analysis. Patients with UCs who had a lower GNRI before treatment had a higher risk of experiencing worse overall survival (HR = 2.62, 95% CI = 1.69–4.09, p < 0.001), recurrence-free survival/progression-free survival (HR = 1.77, 95% CI = 1.51–2.08, p < 0.001), and cancer-specific survival (HR = 2.32, 95% CI = 1.28–4.20, p = 0.006). Moreover, the subgroup analysis did not change the predictive significance of the GNRI in individuals with UCs. Neither Egger’s nor Begg’s test indicated substantial bias in this analysis. Conclusion: As a result of our meta-analysis, we found that a low GNRI strongly predicts poor prognosis for patients with UCs. A lower pretreatment GNRI indicates poor survival outcomes in UCs.